Primer informe del género Gambierdiscus (Dinophyceae) y otros dinoflagelados bentónicos en el Parque Nacional Isla del Coco, Costa Rica, Pacífico Tropical Oriental - Vargas-Montero, Maribelle (2012)
First report of the genus Gambierdiscus (Dinophyceae) and other benthic dinoflagellates from Isla del Coco National Park, Costa Rica, Eastern Tropical Pacific. The Eastern Tropical Pacific is a region reported as free of ciguatera poisoning that causes serious gastrointestinal, neural and cardiovascular problems, even death. But with this study we found a high incidence of benthic microalgae involved in ciguatera poisoning in Isla del Coco National Park (PNIC, from its name in Spanish), Costa Rica. Between 2006 and 2011, during expeditions to PNIC, 420 phytoplankton samples with the interest of finding benthic dinoflagellates involved in the ciguatera poisoning were collected and analyzed. Samples were taken with phytoplankton nets, towed vertically and horizontally or carried by diving, between 5 to 30 m depth, over reef areas, and by direct extraction from benthic macroalgae. We found the dinoflagellates Gambierdiscus spp., Coolia tropicalis, Coolia cf. areolota, Prorocentrum concavum, Prorocentrum compressum, Amphidinium carterae and Ostreopsis siamensis. The quantity of dinoflagellates by macroalgae weight was high, mainly for Gambierdiscus. Ostreopsis and Prorocentrum, the most widely distributed genera throughout the collection sites. Gambierdiscus is a ciguatera producing genus. Two different sizes of Gambierdiscus were found, and comparing our samples with other studies, we conclude that they are different to any previously reported. They possibly represent two new species. Coco Island is an oceanic island and because of its protection status, it is an ideal site for studying the evolution of marine phytoplankton. Also, long-term monitoring is important due to the variety of potentially toxic dinoflagellates living in this marine ecosystem. This is the first study to report benthic dinoflagellates implicated in ciguatera poisoning in other areas of the Eastern Tropical Pacific. Citation: Vargas-Montero, M., Á. MoralesRamírez & J. Cortés. 2012. Primer informe del género Gambierdiscus (Dinophyceae) en el Parque Nacional Isla del Coco, Pacífico Tropical Oriental. Rev. Biol. Trop. 60 (Suppl. 3): 187-199. Epub 2012 Dec 01.